Implementasi Akuntansi Syariah : Tantangan dan Solusi dalam Praktek Bisnis - Faturochman Faturochman; Naufal Riandra Saputra; Tissa Putri Agustin; Peny Cahaya Azwari (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
The implementation of sharia accounting in business practice has become increasingly significant amidst the growing awareness of Islamic values in economic activities. Sharia accounting is not merely a financial recording tool but also a system that upholds principles of justice, transparency, and accountability in accordance with Islamic teachings. However, its application in the business world still faces several challenges, such as limited understanding among business actors, a lack of qualified human resources, and the uneven adoption of sharia accounting standards. This study aims to identify the main challenges in implementing sharia accounting and propose practical solutions in terms of regulation, education, and system innovation. Using a qualitative approach and literature review, the findings indicate that strong collaboration between regulators, academics, and business practitioners is essential to build a sustainable sharia accounting ecosystem that aligns with modern business needs.